Phase I Cardiac Rehabilitation In Patients With Coronary Heart Disease - Yusup Dwiyanto; Kemala Desy; Muhammad Khalid Fredy; Nuzula Firdaus; Desi Luanda; Lusiana Lusiana; Agus Purnama (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This literature study was made by analyzing retrospective minimal scientific articles published in 2010 to 2020 in Indonesian and English. Data obtained from the database includes pubmed, DOAJ, proquest and google scholar with the keywords cardiac rehabilitation, acute coronary syndrome, arrhythmia, acute myocardial infarction, mobilization, six minute walk test and physical exercise. The study results obtained were 8 articles that match the inclusion and exclusion criteria. The results of the study found that implementation of phase I cardiac rehabilitation in patients with CHD accompanied by dysrhythmias/arrhythmias can be recommended for rehabilitation after 12 hours post attack. Phase I cardiac rehabilitation measures begin with education and counseling, exercise or physical activity, breathing exercises, breathing muscle exercises, chest physiotherapy, breathing muscle stretching exercises, and gradual mobilization using the six minute walk test technique